Étude de deux digues d’étangs « en terre » recoupées par le tracé de la RCEA à Pierrefitte-sur-Loire et Coulanges (Allier) - Sophie Liegard; Alain Fourvel (Revue Archéologique du Centre de la France)
The rescue archaeological work linked to the road route of the RCEA in Bourbon Sologne sparked the discovery of two earthen pond dykes. The technical approach of these modern works has been made a priority in order to study their construction method in particular. Apparently homogeneous, it turns out in fact that the improvements belong to two types of dykes developed in accordance with different processes which are still in use nowadays.